The use of a modified Delphi technique to develop a critical appraisal tool for clinical pharmacokinetic studies - Alaa Bahaa Eldeen Soliman (14151519) (2022)
Background Critical appraisal aids in assessing the quality of scientific literature, which is central to the practice of evidence-based medicine. Several tools and guidelines are available for critiquing and assessing the quality of specific study types. However, limited guidance exists for critical appraisal of clinical pharmacokinetic studies. Aim We aimed to achieve experts’ consensus regarding the quality markers for clinical pharmacokinetic studies in an attempt to develop a critical appraisal tool. Method Quality markers related to clinical pharmacokinetic studies, were derived from the published literature and categorized according to manuscript reporting domains (abstract, introduction/background, methodology, results, discussion, and conclusion). Questions that aid in appraising pharmacokinetic studies were formulated from these quality markers. Experts were involved in a modified Delphi process to achieve a consensus regarding the formulated questions. The proposed tool was pilot tested on 30 recently published clinical pharmacokinetic studies. Inter-observer agreement was measured to determine the reliability of the included items. Results Twenty-five experts consented to participate. Three rounds of a modified Delphi survey were required to generate a consensus for a 21-item tool aimed at appraising the quality of clinical pharmacokinetic studies. When applied to 30 recently published clinical pharmacokinetic studies, most items scored fair to moderate levels of agreement (61.90–95.24%). Conclusion The clinical pharmacokinetic critical appraisal tool (CACPK) developed in this study consisted of 21 items aimed at helping an end-user to determine the quality of a pharmacokinetic study. Further studies are warranted to reaffirm the validity and reliability of the CACPK tool. Other Information Published in: International Journal of Clinical Pharmacy License: https://creativecommons.org/licenses/by/4.0 See article on publisher's website: http://dx.doi.org/10.1007/s11096-022-01390-y